Prevention of motion‐induced signal loss in diffusion‐weighted echo‐planar imaging by dynamic restoration of gradient moments. Issue 6 (2nd July 2013) - Gumus, Kazim; Keating, Brian; Poser, Benedikt A.; Armstrong, Brian; Chang, Linda; Maclaren, Julian; Prieto, Thomas; Speck, Oliver; Zaitsev, Maxim; Ernst, Thomas
<x xml:space="preserve">Abstract</x> Purpose Head motion is a significant problem in diffusion‐weighted imaging as it may cause signal attenuation due to residual dephasing during strong diffusion encoding gradients even in single‐shot acquisitions. Here, we present a new real‐time method to prevent motion‐induced signal loss in DWI of the brain. Methods The method requires a fast motion tracking system (optical in the current implementation). Two alterations were made to a standard diffusion‐weighted echo‐planar imaging sequence: first, real‐time motion correction ensures that slices are correctly aligned relative to the moving brain. Second, the tracking data are used to calculate the motion‐induced gradient moment imbalance which occurs during the diffusion encoding periods, and a brief gradient blip is inserted immediately prior to the signal readout to restore the gradient moment balance. Results Phantom experiments show that the direction as well as magnitude of the gradient moment imbalance affects the characteristics of unwanted signal attenuation. In human subjects, the addition of a moment‐restoring blip prevented signal loss and improved the reproducibility and reliability of diffusion tensor measures even in the presence of substantial head movements. Conclusion The method presented can improve robustness for clinical routine scanning in populations that are prone to head movements, such as children and uncooperative adult patients. Magn Reson Med 71:2006–2013, 2014. © 2013 Wiley Periodicals, Inc.